Social Media Monetization Policy in Nigeria: Increasing Consumer Engagement in Digital Marketing with AI - May, Eyeregba Equitozia; Oyekunle, David Oyewumi-Taiwo; Matthew, Ugochukwu Okwudili; Bunmi, Eboesomi Esther; Ugbomeh, Williams Ogochukwu (Recent Research Reviews Journal, 2025)
A key component of digital marketing today is social media monetization, which helps businesses and content creators to make money while increasing customer interaction and product branding. Targeted advertisement, which involves an overall marketing efficiency, have all improved in Nigeria as a result of the use of artificial intelligence (AI) in digital marketing. The regulatory frameworks controlling social media monetization in Nigeria are examined in this study, along with AI-driven marketing strategies and their effects on customer engagement. This study explores Nigeria’s policy, examining its implications for brand strategy, advertising models, and influencer marketing. By integrating governance with market dynamics, businesses can cultivate sustainable digital ecosystems that enhance engagement, transparency, and social value. Effective monetization policies can strengthen Nigeria’s digital economy while aligning corporate interests with broader societal goals, exploring social media monetization policy in Nigeria as a potential avenue for a new social contract as a digital economy development indicator and entrepreneurship sustainability. Promoting a structured and sustainable digital economy, AI-driven monitoring can reduce risks like fraudulent activity, content exploitation, and unequal revenue distribution as digital marketing and brand engineering advance. By regulating brands’ advertisement transparency, AI improves consumer protection by protecting against deceptive marketing and guaranteeing that users see accurate product representations. The study adopted a random sampling technique; 10 real estate companies were selected from the 15 medium-scale real estate companies in the study area. Of the completed questionnaires, 75% were recovered and deemed valuable for the data analysis. The results of the study indicated that a significant portion of medium-scale real estate investment companies generated between 20 million and 100 million in revenue after implementing data-driven product engineering and digital marketing, which is more than they did in the year before digital marketing and product engineering were implemented.